PENGEMBANGAN MODUL EDUKASI KELUARGA ANAK JALANAN DI SIMPANG LAMPU MERAH ARENGKA KOTA PEKANBARU - Wita Andika; Elni Yakub; Rosmawati Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to develop a family education module for street children. This material was prepared using R&D research and development methods. Module Assessment is reviewed from the clarity of the material, systematic material, image support, the suitability of the delivery of the material, and the completeness of the material. The educational module material was validated by 2 BK FKIP UR lecturers, and 2 Guidance and Counseling Teachers. Educational material consists of 3 modules namely, module 1: the importance of the role of fathers and mothers in parenting children, module 2: How to implement 8 family functions, module 3: the impact if the child is on the road & efforts to keep the child from going out. Of the value given by experts, the results of calculations for the clarity aspects of the material obtained a score of 4.75 very clear categories, the systematic aspects of the material obtained a score of 4.0 systematic categories, the aspect of image support obtained a score of 4.5 categories strongly supportive, the aspect of time compatibility Submission of material obtained a score of 4.0 suitable categories, and aspects of completeness of the material obtained a score of 3.75 complete categories, so that for all aspects of material assessment showed that the material developed had met the expected criteria by obtaining a score of 4.2 which was included in the excellent category. The validator also gave the following suggestions, that module 1 should be changed to module 2, to educate more using applicable words, enriched material with different literary sources.Key words: Module, Education, Street children